PENGARUH PEMBERIAN BERBAGAI DOSIS PUPUK NPK DAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM ( Sorghum bicolor L.): PENGARUH PEMBERIAN BERBAGAI DOSIS PUPUK NPK DAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM ( Sorghum bicolor L.) - Pebriana Choirunnisa; Dewi Ratna Nurhayati; Kharis Triyono (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
This study entitled The Effect of Giving Various Doses of NPK Fertilizer and Goat Manure on the Growth and Yield of Sorghum (Sorghum bicolor L), aims to determine the effect of giving various doses of NPK fertilizer and goat manure on the growth and yield of sorghum plants, carried out starting in May 2021. until August 2021, at the Green House or Experimental Garden of the Slamet Riyadi Faculty of Surakarta, which is located in Kadipiro Village, Kec. Banjarsari, Surakarta City, Central Java with an altitude of ± 105 meters above sea level and the type of soil is Alluvial. This study used a completely randomized design (CRD) method which was arranged in a factorial manner consisting of 16 treatments, each treatment repeated 3 times. The fertilizers used are NPK fertilizer and goat manure. The data from this study were analyzed using the BNJ test (Real Honesty Difference) at the level of 5%. Parameters observed included plant height, number of leaves, fresh weight of seeds per panicle, dry weight of seeds per panicle, weight of 1000 seeds, number of seeds per panicle, weight of wet stover, weight of dry stover, and panicle length. The results showed that: 1 Treatment of goat manure dose of 70 g/plant gave the best results on the weight parameter of 1000 seeds and treatment of goat manure dose of 105 g/plant gave the best results on the weight of wet stover. (2)NPK fertilizer treatment of 8 g/plant gave the best results on the number of leaves parameters, NPK fertilizer treatment of 6 g/plant gave the best results on the parameters of dry weight of seeds per panicle and number of seeds per panicle. While NPK fertilizer 8 g/plant gave the best results on the parameters of wet weight of seeds per panicle and dry weight of stover, NPK fertilizer treatment of 6 g/plant gave the best results on parameters of wet stover weight.(3) The interaction between the dose of goat manure (K) and NPK fertilizer (N) did not affect all observations.